1994
DOI: 10.1287/mnsc.40.7.846
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Heuristic Worst-Case Performance Analysis of the Two-Level Network Design Problem

Abstract: This paper studies a multi-facility network synthesis problem, called the Two-level Network Design (TLND) problem, that arises in the topological design of hierarchical communication, transportation, and electric power distribution networks. The nodes of a multi-level network have varying levels of importance; more critical or higher level nodes require more expensive higher grade interconnections. Given an undirected network with L possible facility types for each edge, and a partition of the nodes into L lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 76 publications
(42 citation statements)
references
References 15 publications
0
42
0
Order By: Relevance
“…Therefore, Theorem 1 implies that the worst-case ratio of the composite heuristic for TLND problems with 10-proportional costs must not exceed 2. These worst-case bounds for the composite heuristic for HND and TLND problems are tight (Balakrishnan et al [1992a]). …”
Section: Applications Of General Worst-case Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Therefore, Theorem 1 implies that the worst-case ratio of the composite heuristic for TLND problems with 10-proportional costs must not exceed 2. These worst-case bounds for the composite heuristic for HND and TLND problems are tight (Balakrishnan et al [1992a]). …”
Section: Applications Of General Worst-case Resultsmentioning
confidence: 91%
“…Another recent stream of research in the network design literature attempts to provide reliable designs by using multiple interconnection technologies. Examples are the Hierarchical Network Design Problem (Current, Revelle, and Cohon [1986]) and the more general Multi-Level Network Design Problem (Balakrishnan, Magnanti, and Mirchandani [1992a]); this "serviceability" approach to network design provides higher grade (more reliable and more costly) service between certain "important" pairs of nodes, and lower grade service between other nodes. This approach does not incorporate multiple paths.…”
Section: Introductionmentioning
confidence: 99%
“…Since PB = 1, Theorem 1 implies that the worst-case ratio of the composite heuristic does not exceed 2. Balakrishnan et al [1992] have previously described worst-case examples for the HND and TLND problems showing that these bounds are tight. By using a more sophisticated heuristic for the overlay subproblem, e can improve the worst-case bound.…”
Section: Theoremmentioning
confidence: 99%
“…For the HND problem, the BU heuristic finds an MST of graph G using primary costs cj, and installs primary facilities on all edges of this tree. In our subsequent -5-analysis, we ignore the possibility of further reducing the cost of the BU heuristic solution by locally downgrading some primary facilities into secondary facilities whenever possible (for the HND problem, Balakrishnan et al [1992] have shown that local improvement does not reduce the heuristic's worst-case performance ratio).…”
Section: Composite Heuristic For Overlay Optimizationmentioning
confidence: 99%
See 1 more Smart Citation